The PJBL Model on Increasing the Pancasila Student Profile (P3) of Grade IV Elementary School Students - Raja Elinda Prawati; Zaka Hadikusuma Ramadan (Universitas Pendidikan Ganesha, 2023)
This research is motivated by problems regarding the profile of Pancasila students, students who still need to improve, such as children who are still lazy to read books, do not want to work together, and are less independent in doing assignments. This study aims to analyze the effectiveness of the PJBL model in increasing the profile of Pancasila students (p3) in fourth-grade elementary school students. This type of research uses a quantitative approach with an experimental research design. The population of this study is class IV which consists of 3 classes. While the research sample used a purposive sampling technique, the research sample was in the IVC class with 25 students. Data collection techniques using questionnaires and documentation. Instrument testing uses validity and reliability. Data analysis techniques used descriptive analysis and prerequisite tests, namely normality, homogeneity, hypothesis, and N-Gain tests. Based on research data processing, the PJBL model is quite effective in increasing the profile of Pancasila students (P3) in class IV elementary school students. It is proven by the t-count results, namely that there is an increase in the profile of Pancasila students (P3) of students with the PJBL model who are in the medium category, where the N-Gain value is 0.56. It was concluded that the PJBL model could increase the profile of Pancasila students (P3) in grade IV elementary school students. It is proven by the t-count results, namely that there is an increase in the profile of Pancasila students (P3) of students with the PJBL model who are in the medium category, where the N-Gain value is 0.56. It was concluded that the PJBL model could increase the profile of Pancasila students (P3) in grade IV elementary school students. It is proven by the t-count results, namely that there is an increase in the profile of Pancasila students (P3) of students with the PJBL model who are in the medium category, where the N-Gain value is 0.56. It was concluded that the PJBL model could increase the profile of Pancasila students (P3) in grade IV elementary school students.